Defect Automatic Identification of Eddy Current Pulsed Thermography. (31st December 2014) - Chen, Kai; Bai, Libing; Chen, Yifan; Cheng, Yuhua; Tian, Shulin; Zhu, Peipei
Abstract : Eddy current pulsed thermography (ECPT) is an effective nondestructive testing and evaluation (NDT&E) technique, and has been applied for a wide range of conductive materials. Manual selected frames have been used for defects detection and quantification. Defects are indicated by high/low temperature in the frames. However, the variation of surface emissivity sometimes introduces illusory temperature inhomogeneity and results in false alarm. To improve the probability of detection, this paper proposes a two-heat balance states-based method which can restrain the influence of the emissivity. In addition, the independent component analysis (ICA) is also applied to automatically identify defect patterns and quantify the defects. An experiment was carried out to validate the proposed methods.